KONVERGENSI MEDIA DALAM PROGRAM “AFTER HOURS WITH HELMY YAHYA” DI INEWS - Irmawati Oktavianingtyas; Udi Rusadi (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2021)
After Hours with Helmy Yahya is a talk show program produced by Inews TV, under the auspices of the MNC Group. But unfortunately the program was terminated after airing for no more than 2 months. Convergence as a strategy for media companies to survive in the digital era has been applied to the program, but apparently this does not affect the success of the program. Therefore, the author wants to know the application of media convergence in the "After Hours with Helmy Yahya" program and also to know the extent to which convergence contributes to the success of the program, especially in terms of the political economy of the media. The results of the study indicate that most of the program's income comes from After Hours with Helmy Yahya which broadcasted via analog TV. It can be concluded that the convergence strategy has not contributed significantly to the success of the program, especially in terms of income for the company.Keywords: The Political economy of media, Media Convergence, Inews.Abstrack: After Hours with Helmy Yahya merupakan program talkshow besutan Inews TV, dibawah naungan MNC Group. Namun sayangnya program tersebut diberhentikan setelah tayang tidak lebih dari 2 bulan. Konvergensi yang digadang-gadang sebagai sebuah strategi perusahaan media untuk bertahan di Era digital telah diterapkan pada program tersebut, namun tampakhnya hal ini tidak mempengaruhi keberhasilan program. Oleh karena itulah penulis ingin mengetahui penerapan konvergensi Media Dalam Program “After Hours with Helmy Yahya” dan sejauh mana konvergensi berkontribusi pada keberhasilan program, terutama dari sisi ekonomi politik media. Hasil penelitian menunjukkah bahwa Sebagian besar pendapan program masih berasal dari tayangan After Hours with Helmy Yahya yang disiarkan melalui TV analog, dengan begitu strategi konvergensi yang dilakukan belum berkontribusi secara signifikan dalam keberhasilan program tersebut, terutama dari sisi pemasukan untuk perusahaan.Kata Kunci: Ekonomi Politik Media, Konvergensi Media, Inews.